1970
DOI: 10.1029/jb075i029p05713
|View full text |Cite
|
Sign up to set email alerts
|

Reflection ofPP′ seismic waves from discontinuities in the mantle

Abstract: A systematic study of the travel times and apparent velocities of precursors of the seismic core phase PKPPKP indicate that these phases are reflections from the mantle. The strongest reflection is from a depth of 630 km. In order of confidence, other reflectors were found at depths of 280, 520, 940, 410 (very weak), and 1250 km (tentative). The weakne• of the 410-km reflection was surprising in view of the large velocity increase at this depth indicated by refraction and Love-wave studies. This transition reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(59 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…From this system to whole mantle convection on the other end, the degree of depression is expected to be smaller. Observationally, a sharp 670-km discontinuity has previously been suggested based on precursors to P'P', denoted by P'610P' [e.g., Engdahl and Flinn, 1969;Whitcomb and Anderson, 1970;Richards, 1972;Husebye et al, 1977;Nakanishi, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…From this system to whole mantle convection on the other end, the degree of depression is expected to be smaller. Observationally, a sharp 670-km discontinuity has previously been suggested based on precursors to P'P', denoted by P'610P' [e.g., Engdahl and Flinn, 1969;Whitcomb and Anderson, 1970;Richards, 1972;Husebye et al, 1977;Nakanishi, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for large-scale stratification of the mantle includes tomographic patterns and spectra [e.g., Tanimoto, 1990;Scrivner and Anderson, 1992;Ray and Anderson, 1994;Wen and Anderson, 1995;Gu et al, 2001;Anderson, 2002a;Becker and Boschi, 2002;Trampert et al, 2004], dynamic topography and evidence for slab flattening, and apparent pileups [Fukao et al, 1992[Fukao et al, , 2001. Support for a complication, discontinuity, or barrier near 900-km depth is widespread [Whitcomb and Anderson, 1970;Tanimoto, 1990;Revenaugh and Jordan, 1991;Kawakatsu and Niu, 1994;Ritzwoller and Lavely, 1995;Wen and Anderson, 1995;Forte and Mitrovica, 2001;Shen et al, 2003;Mattern et al, 2004]. The tomographic structure of the mantle above the Repetti discontinuity-the upper mantle proper-correlates with present and past plate tectonics [Wen and Anderson, 1995;Becker and Boschi, 2002] and behaves as expected for fluid with a moderate Rayleigh number: cooled from above and driven by the plates and lithospheric architecture.…”
Section: Chemical Discontinuities?mentioning
confidence: 99%
“…5(b). The precursors to P'P' (P'dP': d=410 or 660), which are underneath reflections at velocity discontinuities in the mantle, offer valuable information on the velocity jump, exact depths, and thicknesses of the transition zones (e.g., Engdahl and Flinn, 1969;Whitcomb and Anderson, 1970). Nakanishi (1988) showed the precursors to P'P' from the 660 and 410 km discontinuities beneath the midAtlantic ridge using waveforms from two events (mb =6.4 and 6.8) occurring in the Fiji and Tonga regions, obtained at stations of Hokkaido University.…”
Section: Overall Characteristics Of J-array Seismogramsmentioning
confidence: 99%
“…Furthermore, there are several studies that support the existence of steep velocity gradient or discontinuity at the depth of around 1,200 km. In the pioneering study on precursors to P'P' by Whitcomb and Anderson (1970), very weak reflections at the 1,250 km depth were observed at stations in the United States, from events occurring in South America. Stunff et al (1995) revealed reflections at the depths of 785 and 1,180 km beneath the southern African rift.…”
mentioning
confidence: 99%